Asian medical industries : contemporary perspectives on traditional pharmaceuticals - Kloos, Stephan; Blaikie, Calum (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2022)
This book develops the concept of Asian Medical Industries as a novel perspective on traditional Asian medicines. Complementing and updating existing work in this field, the book provides a critical and comparative analytic framework for understanding Traditional Chinese Medicine, Ayurveda, Sowa Rigpa, and Japanese Kampō in the 21st century. No longer subaltern health resources or conservative systems of traditional knowledge, these medicines become an integral part of modern Asia as innovative, lucrative industries. Ten original case studies employ insights from anthropology, history, geography, and economics to trace the transformation of Asian medical traditions into rapidly growing and dynamic pharmaceutical industries. Collectively, these contributions identify this as a major phenomenon impacting Asian and global healthcare, economics, cultural politics, and environments. The book suggests that we can learn more about Asian medicines today by approaching them as industries rather than as cultural or epistemic systems. Asian Medical Industries is a highly original resource for students and scholars across a range of academic fields such as anthropology, history, and Asian studies, as well as medical practitioners, health sector actors, and policymakers.
Part 1: East Asian Medical Industries1. Discovering New Drugs in Traditional Chinese Medicine: Inside Guangzhou Huahai Pharmaceuticals Liz P. Y. Chee2. Cultivation and Paternalism in the Service of the Market: Medical Industry and Ethnicity in Southwest China Manuel Campinas3. The Development of the Kampo Medicines Industry: 'Good Practices' and Health Policy-Making in Japan Ichiro Arai, Julia Yongue, and Kiichiro Tsutani4. The Pharmaceutical Industry of Toyama Prefecture, Japan: Haichi Household Medicines, Intersectoral Collaboration and Industrial ClusteringTomoko Futaya & Calum BlaikiePart 2: South Asian Medical Industries 5. Globalizing Ayurveda, Branding India: Implications for the Ayurvedic Pharmaceutical Industry Chithprabha Kudlu6. Industry Dynamics and Clustering in Ayurvedic Pharmaceutical Production in South India: The Case of CARe Keralam Harilal Madhavan & Sajitha Soman7. Untangling the Web of Raw Material Supply for the Ayurvedic Industry: The Complex Geography of Plant Circulations Lucie Dejouhanet & Sreelakshmy M.Part 3: Sowa Rigpa Industries8. "Sourcery": Losing Track of Tibetan Medicinal Plants between Commerce and Conservation in Northern India Jan van der Valk9. Making Tibetan Medicine in Nepal: Industrial Aspirations, Cooperative Relations, and Precarious Production Calum Blaikie & Sienna Craig10. The Emergence of the Traditional Mongolian Medicine Industry: Communism, Continuity and Reassemblage Stephan Kloos
Keywords: Medical care -- Asia; Traditional medicine -- Asia; MEDICAL / General; MEDICAL / Research